PUSTAKAWAN MASA LALU, SEKARANG DAN AKAN DATANG SEBAGAI SUMBER INFORMASI DALAM PENDIDIKAN - Khadijah Khadijah; Afrizal Afrizal (UIN Imam Bonjol Padang, 2020)
Abstract: The term Librarian is very unfamiliar in the midst of society. Because the term librarian is something people rarely hear. Because the librarian is very closely related to the library in the people's understanding that the library is a warehouse filled with piles of books that are worn and unkempt. After that, the Law of the Republic of Indonesia number 43 of 2007 Librarians have been recognized by the state as technical educational functional personnel, so that they are equal to other functions. Such as functional analysis of positions, researchers and others. This paper presents the history and description of the library's past, present and future. Among these challenges include global competition, free trade in the Asean / MEA economic community, Human Resources Development, language skills, managerial skills, mastery of technology, communication skills and scientific skills.Keywords: Librarian, Information Sources in Education, LibraryAbstrak: Istilah Pustakawan memang sangat asing sekali di tengaah-tengah masyarakat. Sebab, istilah pustakawan suatu hal yang jarang didengar orang. Hal ini dikarenakan perpustakaan itu erat berkaitan dengan pemahaman masyarakat yang menganggap perpustakaan itu adalah sebuah gudang yang dipenuhi oleh tumpukan buku yang sudah kumal dan tidak terawat lagi. Setelah itu undang undang RI nomor 43 tahun 2007 Pustakawan sudah diakui oleh negara sebagai tenaga fungsional teknis kependidikan, sehingga mereka sudah setara dengan fungsional lainnya. Seperti fungsional analisis jabatan, peneliti dan lain-lain. Tulisan ini menyajikan History dan penjelasan perpustakaan masa lalu, sekarang dan akan datang. Diantara tantangan tersebut diantaranya seperti persaingan global, perdagangan bebas masyarakat ekonomi Asean/ MEA, Pembinaan SDM, Kemampuan berbahasa, kemampuan manajerial, penguasaan teknologi, kemampuan dalam berkomunikasi dan keterampilan ilmu pengetahuan.Kata Kunci: Pustakawan, Sumber Informasi dalam Pendidikan, Perpustakaan